A case study of Giordano : its human resource strategies - Loh, Wai Fong (2014)
The trend towards globalisation has resulted in an increase in the intensity and diversity of competition faced by organisations. Consequently, a firm should adopt strategic management techniques so as to better adapt to changes in the highly dynamic environment.